The M&A Short-Term Wealth Effect of A Consistent Dividend-Paying Firm - Veeghan Frances Tirtasaputra; Veren Geby Salim; John Iwan Kusno; Adrian Teja (Jurnal Keuangan dan Perbankan, 2022)
AbstractThe paper examines the MA short-term wealth effect of a consistent dividend-paying firm. The consistent dividend-paying firm is unique because they are associated with lower agency problems. Hence, it is expected that the MA by the dividend-paying firm has a short-term positive wealth effect. To test the hypothesis, we perform two steps analysis. The event-study method examines the acquirer stock performance on the announcement date, the deal close date, and the announcement to deal close date. The cross-section regression to test the short-term wealth effect of MA by the dividend-paying firm. The dependent variable is the acquirer's stock performance from the event-study method. The independent variable is a dividend-paying firm. The control variables are the acquisition deal value relative to the acquirer's stock market capitalization, the acquirer's stock dividend yield, and the acquirer's price-to-book value (PBV) ratio. The samples are MA transactions in ASEAN-5 (Indonesia, Malaysia, The Philippines, Thailand, and Vietnam) for 2015-2019. The regression analysis shows that the variable representing a dividend- paying firm has a negative sign. The finding suggests that investors react negatively to the MA by the dividend-paying firm. The negative wealth effect is relatively small compared to the MA deal value and the acquirer's stock valuation. The result is that the MA by a dividend-paying firm provides a short-term positive wealth effect.JEL: G34, G35